Providing Support Differentially Affects Asian American and Latinx Psychosocial and Physiological Well-Being: A Pilot Study - Guan, Shu-Sha Angie; Jimenez, Gabriela; Cabrera, Jennifer; Cho, Anna; Ullah, Omar; Den Broeder, Ruben (Frontiers in Psychology, 2022)
Although substantial evidence suggests receiving social support has positive implications for well-being, less is known about how providing support can confer benefits, particularly for Asian American and Latinx individuals who are more likely to come from interdependent cultures that emphasize family obligation. Asian American and Latinx college students (N = 48; Mage = 21.44, SD = 2.61; 68.75% female) reported on pre-task anxiety before taking part in a modified laboratory task that elicits a physiological stress response as measured by total cortisol output. They were randomly assigned to write (a) a supportive note to a family member, (b) supportive note to a close friend, or (c) about their day in a control condition after the mild lab stressor and reported on psychosocial well-being (i.e., post-task anxiety, self-esteem). Those who provided support to a family member experienced higher self-esteem compared to those in the control condition. However, there was variation in Asian American and Latinx participants’ physiological stress response (i.e., total cortisol output). The findings suggest that providing support to close others, particularly family members, can be differentially meaningful for individuals from diverse backgrounds.